“1945” as a Turning Point in German Art History? Challenging the Paradigm of Rupture and Discontinuity - Fuhrmeister, Christian (Artium Quaestiones, 2019)
The historiographical article looks at “1945” as a turning point, inquiring whether the end of both the Second World War and National Socialism also implied a radical break for art history in Germany. In evaluating both contemporary perspectives (like Herbert von Einem’s opening lecture of the First German Art Historians Meeting in 1948) and recent historiographical studies, the paper questions the concept of “Stunde Null” or “hour zero,” and intends to challenge the established paradigm of rupture and discontinuity. Arguing for a more nuanced and holistic understanding of the transformation processes in the postwar situation, three major reasons are identified why simplistic categorizations often prevail: (1) a very narrow definition of the art historian in the history of art history, (2) the disjunction between the humanities and the larger political context, which allow the individual to imagine himself/herself untainted and uncompromised by ideology, and (3) the high degree of continuity, in particular if compared to the radical changes that took place in 1933. The article thus resumes that the idea of “turning points” deserves further differentiation, and calls for the integration of the political dimension into historiography. Essentially, the challenge remains to distinguish between factual processes, false or fraudulent labelling, and symbolic gestures.